Peningkatan Belajar Siswa Dalam Pembelajaran IPS Dengan Model Snowball Throwing Di Kelas V Sekolah Dasar - Darlis, Rini; Farida S., Farida S.; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to describe the plan, the learning process and the improvement of the student, learning achievemntin Social Studies in the grade V of SDN 20 V Koto Kampung Dalam Padang Pariaman` The data of the research were the Lesson plan, the teacher and the student` activities, and the student` learning achievement. the result of the research indicated that from the first cycle to the second one, the score of the Lesson Plan Increased from 79% to 96%, the teacher`s aspect increased from 79% to 95%, the student`s aspect from 72% to 93%. keyword : Social Science learning achievement, Social Science learning process, Snowball Throwing